PENERAPAN MODEL GROUP INVESTIGATION DALAM MENINGKATKAN KETERAMPILAN MENULIS KREATIF SISWA KELAS V DI MI DATOK SULAIMAN PALOPO - Kamriani Kamriani (IAIN Palopo, 2019)
The main problem in this research is that students find it difficult to find ideas about the material they want to write and students also do not participate in learning activities. The things to be achieved in this study are to find out whether there is an increase in students' creative writing skills and to find out whether students can be more active in the learning process activities. This research is a classroom action research (CAR) which consists of two cycles, each cycle carried out in 3 meetings, with stages of Planning, Implementation, Observation, and Reflection. The subjects of this study were fifth-grade students of MI Datok Sulaiman Palopo, which numbered 35 students. The results showed that: with the implementation of the Group Investigation model can improve learning outcomes and activate students in the learning process, each cycle experienced an increase. Based on the test of learning outcomes of students in the fifth grade of MI Datok Sulaiman Palopo, two cycles showed that student learning outcomes from the first cycle were 53.71 while the second cycle was 81.57 and had fulfilled the KKM value of 70